Thermal Comfort Study in Vibration and Noise Laboratory at UTHM Pagoh - 'Ain Hasanah Rastu Chemerlang,; Kamarul Aini Mohd Sari, (Progress in Engineering Application and Technology, 2025)
Thermal comfort has a direct impact on people's health, well-being, and productivity. The purpose of this study is to assess thermal comfort in the Vibration and Noise Laboratory (MTGDK) UTHM Pagoh in response to student concerns regarding uncomfortably lecture situation. The objectives of this study are to identify and measure key thermal discomfort parameters and analyze the thermal comfort condition in laboratory. The method used to collect data in the MTGDK laboratory is physical measurement (air temperature, relative humidity, air velocity and mean radiant temperature) and questionnaire survey. Thermal comfort parameters were analyzed and compared standard and guidelines. The collected data did not fully comply with the accuracy requirements set by ASHRAE Standard 55. The Predicted Mean Vote (PMV) from measurement value of 0.1, the Predicted Percentage Dissatisfied (PPD) was 5%. Additionally, values obtained using the CBE Thermal Comfort Tool value of PMV of -0.85 and a PPD of 20%, and through questionnaire survey yielded a PMV of +1.9 and a PPD of 71%. The analysis of pearson correlation shows that the relationship between PMV with parameter showed very weak linear correlation. These different results raise highlight important differences and show that the MTGDK laboratory was in a thermally uncomfortable state. In conclusion, the findings of this study indicate that the thermal conditions in the laboratory do not comply with ASHRAE standards and improvements are needed, particularly in controlling indoor humidity and adjusting air-conditioning temperature, to enhance user satisfaction, and support the development of a sustainable and conducive learning environment.